2014
DOI: 10.2147/tcrm.s71749
|View full text |Cite
|
Sign up to set email alerts
|

Patient risk factors for developing a drug-related problem in a cardiology ward

Abstract: BackgroundBecause of the high incidence of drug-related problems (DRPs) among hospitalized patients with cardiovascular diseases and their potential impact on morbidity and mortality, it is important to identify the most susceptible patients, who therefore require closer monitoring of drug therapy.PurposeTo identify the profile of patients at higher risk of developing at least one DRP during hospitalization in a cardiology ward.MethodWe consecutively included all patients hospitalized in the cardiology ward of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
55
5
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 28 publications
(40 reference statements)
13
55
5
5
Order By: Relevance
“…High numbers of available medications and associated comorbidities have resulted in polypharmacy worldwide . Polypharmacy is an increasing problem in the care of multimorbide patients, leading to increased treatment‐related problems (TRPs), hospital emergency department visits and hospitalisation rates . Irrational drug use has also been associated with high occurrence of TRPs which is a major concern in health care leading to increased morbidity and total healthcare costs .…”
Section: Introductionmentioning
confidence: 99%
“…High numbers of available medications and associated comorbidities have resulted in polypharmacy worldwide . Polypharmacy is an increasing problem in the care of multimorbide patients, leading to increased treatment‐related problems (TRPs), hospital emergency department visits and hospitalisation rates . Irrational drug use has also been associated with high occurrence of TRPs which is a major concern in health care leading to increased morbidity and total healthcare costs .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, polypharmacy increases the risk of a drug-related problem (DRP), defined as an event or circumstance involving drug therapy that can interfere with a desired health outcome. 9 The occurrence of DRPs can reduce the benefits of drugs and cause increased morbidity and mortality. 10 According to the classification scheme of the Pharmaceutical Care Network Europe Foundation (PCNEF), four types of DRPs exist, including drug effects, adverse drug reactions (ADRs), treatment cost-related problems and other problems.…”
mentioning
confidence: 99%
“…20 Other studies conducted on the cardiology ward, reported DDI and drug-food interactions frequency altogether or assessed only DDIs in the heart failure patients. 21,22 The potential of using supporting electronic systems to manage pDDIs in CVD patients was not assessed. In this regard, the aim of the study was to describe the type and prevalence of potentially relevant pDDIs in CVD patients, and to assess the concurrent exposure to additional risk factors such as renal or liver disease, which may further affect drug exposure and therapy outcomes.…”
mentioning
confidence: 99%